Первая находка ископаемых остатков косматых хомяков — Lophiomyinae (Rodentia, Cricetidae) - Топачевский, В.А.; Скорик, А.Ф. (Вестник зоологии, 1984)
The First Find of a Lophomyinae (Rodentia, Cricetidae) Fossil Representative. Topacevski V. A., Skorik A. F.— Vestn. zool., 1984, No. 2. Microlophiomys gen. n. (type species
by original designation and monotypy: Microlophiomys vorontsovi sp. n.) differs from the
recent Lophiomys by remarkably smaller size, enlargel MI crown, as well as by dimentional ratios and position of the M¹ anterocone trilophus pattern; mesoanterocone exceeds
the size of intero- and exteroanterocone and is closer to the first. Type material:
a single M¹ sin. Type locality: Lower Macotis deposits outcropped at Novoukrainka
village, Razdelnaya distr., Odessa region, Ukrainian SSR. 1t is the very first find of the
fossil subfamily representative, far outside the range of the recent forms: Sudan, Ethiopia, Somali, Kenya, Uganda, Tanzania.